BLOCKCHAIN IMPLEMENTATION FOR NOKA COFFEE JAMBI SUPPLY CHAIN TRANSPARENCY AND TRACEABILITY: ISLAMIC BUSINESS PERSPECTIVE - Allimmah, Khoirunnisa Nurul; Ridwansyah, Ridwansyah; Rosilawati, Weny (Distribusi - Journal of Management and Business, 2025)
The significant increase in coffee consumption in Indonesia highlights the importance of a deep understanding of the complex coffee supply chain. In addition to consumption regulations in Islam, society is also faced with various scandals and food safety incidents, making clear information about the origins, production processes, and safety of the products to be consumed essential. The aim of this research is to explore the opportunities and challenges of implementing blockchain technology to enhance transparency and traceability in the supply chain, viewed from the perspective of Islamic business at Noka Coffee. This study adopts a qualitative descriptive research method and utilizes primary data obtained from structured interviews conducted via Zoom Meeting with stakeholders in the Noka Coffee supply chain. The results indicate that although there are substantial potential benefits from the use of blockchain technology, its implementation also faces several challenges. These challenges include high implementation and maintenance costs, organizational culture, and consumer behavior. Therefore, collaboration among coffee shops, farmers, technology developers, and consumers is crucial to address these challenges and enhance technology adoption. The findings of this research contribute to the development of a complex and sustainable supply chain. With blockchain as an instrument, it is hoped that a more transparent and traceable system can be created, in accordance with Sharia principles. This initiative not only has the potential to increase consumer trust but also supports more responsible and sustainable business practices in the coffee sector.